Development and Implementation of an Acute Kidney Injury Remote Patient Monitoring Program: Research Letter - Charkviani, Mariam; Barreto, Erin F.; Pearson, Kristina K.; Amberg, Brigid M.; Amundson, Rachel H.; Bell, Sarah J.; Cleveland, Eric J.; Daniels, Craig E.; Kohler, Christopher M.; Leuenberger, Angela M.; Philpot, Lindsey M.; Ramirez, David A.; et al. (Canadian journal of kidney health and disease, 2023)
Acute kidney injury (AKI) survivors have a dynamic posthospital course which warrants close monitoring. Remote patient monitoring (RPM) could be used to improve quality and efficiency of AKI survivor care. Objective: The objective of this report was to describe the development and preliminary feasibility of an AKI RPM program launched in October 2021. Setting: Academic medical center. Patients: Patients enrolled in the AKI RPM program were those who experienced AKI during a hospitalization and underwent nephrology consultation. Measurements/Methods: At enrollment, patients were provided with home monitoring technology and underwent weekly laboratory assessments. Nurses evaluated the data daily and adhered to prespecified protocols for management and escalation of care if needed. Results: Twenty patients were enrolled in AKI RPM in the first 5 months. Median duration of program participation was 36 (31, 40) days. Eight patients (40%) experienced an unplanned readmission, or an emergency department visit, half (N = 4) of which were attributed to AKI and related circumstances. Of the 9 postgraduation survey respondents, all were satisfied with the RPM program and 89% would recommend RPM to other patients with similar health conditions. Limitations: Acute kidney injury RPM was made possible by the existing infrastructure in our integrated health system and the robust resources available in the Mayo Clinic Center for Digital Health. Such infrastructure may not be universally available which could limit scale and generalizability of such a program. Conclusions: Remote patient monitoring can offer a unique opportunity to bridge the care transition from hospital to home and increase access to quality care for the AKI survivors.